Pham et al. (2021) Notes on the genus Chamaeanthus (Orchidaceae, Epidendroideae, Vandeae, Aeridinae) with a new species from Vietnam. Phytotaxa 524 (2): 131–134. - Pham, Phuoc Dien; Kumar, Pankaj; Dang, van Son; Nguyen, Dinh Hiep; Bui, van Huong; Tu, Bao Ngan; Dang, Minh Quan; Truong, Ba Vuong (Phytotaxa, 2021)
N/A